DEPLOYMENT OF SMART CONTRACTS ON BLOCKCHAIN TECHNOLOGY IN EARLY MITIGATION OF DISTRIBUTED DENIAL OF SERVICE IN SOFTWARE DEFINED NETWORKS (Nigerian Journal of Technology, 2025)
The rapid growth of smart and mobile devices that have resulted in content proliferation, server virtualization, and the emergence of cloud services have compelled the communication network industry to re-examine its network topologies. In this work, Distributed Denial of Service (DDoS) attacks are conducted by flooding target systems with traffic, designed to disrupt or suspend internet services for use by legitimate users. These attacks deplete network resources, thereby disabling those services and in turn decreasing the availability of the network. Blockchain technology has emerged as a viable option for DDoS mitigation. This technology has blockchain's core and promising inherent features to combat fatal cyber threats. These features include but are not limited to decentralization, immutability, integrity, anonymity, and verifiability. This work models a Software Defined Network (SDN) that is capable of mitigating DDoS attacks by integrating smart contracts. This offers a security technique that combines SDN and Blockchain to mitigate DDoS attacks at early stage. Intrusion detection and prevention are essential components of a comprehensive network protection strategy and are employed to detect and mitigate DDoS attacks in the SDN. In this paper, a secure network architecture capable of mitigating DDoS attacks in less than a second through the use of Blockchain technology has been presented after deployment. With a maximum of 25 requests per second for a single user and 8,000 compromised nodes, the software defined network successfully mitigated the DDoS at 0.68 seconds.